Critical Discourse Analysis on King Salman’s Speeches at the United Nations General Assembly - Reflinaldi, Reflinaldi; Hadi, Syofyan; Khairunnisa, Annisa; Fitrah, Azizah; Rahmi, Awliya; Rezi, Melisa (Humanus, 2024)
This study aims to reveal the ideology in King Salman's political speeches at the United Nations General Assembly. A critical qualitative design was applied in analyzing two of King Salman's speeches in 2020 and 2021. In line with the research objectives, the ideological square is used as the theoretical framework for data analysis. The results of microanalysis show that King Salman uses the basic strategy of emphasizing positive things about 'us' in 129 data (58.6%), emphasizing negative things about 'them' in 60 data (27.3%), and de-emphasizing positive things about 'them' in 31 data (14.1%). As for de-emphasizing negative things about ‘us’ not found in the data source. In the microanalysis dimension, among the rhetorical discursive strategies found were actor description in 77 data (35.0%), consensus in 16 data (7.3%), comparison in 6 data (2.7%), values expression in 76 data (34.5%), victimization-criminalization in 30 data (13.6%), and national self-glorification in 15 data (16.9%). Based on this analysis, the general ideologies found in King Salman's speech are nationalism and anti-imperialism. King Salman constructed Saudi Arabia's national identity in international eyes as a philanthropist, humanitarian, peace initiator, and non-violence country. These identities are then represented as the trademark of Saudi Arabia's foreign policy.